Anode composition, anode for lithium secondary battery including the same, and lithium secondary battery including the anode
The silicon-based negative electrode composition with a carbon-coated active material and a rubber-based binder system addresses volumetric expansion and gas issues, enhancing battery performance and energy density in lithium secondary batteries.
Patent Information
- Application Number
- JP2024539731
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-22
- Filing Date
- 2023-06-22
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-06-22
AI Technical Summary
Silicon-based negative electrodes in lithium secondary batteries face issues of volumetric expansion and gas generation due to hydration by -OH groups, leading to disrupted conductive paths and reduced battery performance.
A negative electrode composition featuring a silicon-based active material coated with carbon and a binder system comprising a rubber-based binder in excess of a water-based binder, which maintains contact and minimizes conductive material to reduce tortuosity and diffusion resistance.
The composition effectively suppresses gas generation and enhances slurry stability, maintaining conductive paths, and improves energy density and cycle life by reducing conductive network disruptions during charging and discharging.
Smart Images

Figure 2025501277000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of the filing date of Korean Patent Application No. 10-2022-0076787, filed with the Korean Intellectual Property Office on June 23, 2022, the entire contents of which are incorporated herein by reference.
[0002] The present application relates to a negative electrode composition, a negative electrode for a lithium secondary battery including the same, and a lithium secondary battery including the negative electrode. [Background technology]
[0003] The rapid increase in the use of fossil fuels has led to an increased demand for alternative and clean energy, and one of the most actively researched fields in this area is power generation and storage using electrochemical reactions.
[0004] At present, secondary batteries are a typical example of electrochemical elements that utilize such electrochemical energy, and the range of their use is expanding more and more.
[0005] As technological development and demand for mobile devices increases, the demand for secondary batteries as energy sources is rapidly increasing. Among such secondary batteries, lithium secondary batteries, which have high energy density and voltage, long cycle life, and low self-discharge rate, are commercialized and widely used. In addition, research into a method for manufacturing a high-density electrode having a higher energy density per unit volume as an electrode for such high-capacity lithium secondary batteries is actively being conducted.
[0006] In general, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode includes a negative electrode active material that inserts and releases lithium ions released from the positive electrode. Silicon-based particles having a large discharge capacity may be used as the negative electrode active material.
[0007] In particular, in response to the recent demand for high-density energy batteries, active research is being conducted into methods of increasing capacity by using silicon-based compounds such as Si / C and SiOx, which have a capacity 10 times larger than that of graphite-based materials, as negative electrode active materials. However, silicon-based compounds, which are high-capacity materials, have a larger capacity than the graphite that has been used traditionally, but they have the problem that their volume suddenly expands during charging, cutting off the conductive path and reducing the battery characteristics.
[0008] To solve this problem, we conducted research to use SBR-CMC binders with excellent elongation properties instead of water-based binders (PAA, PAM, etc.) with high modulus that are used in conventional silicon-based anodes. In this case, problems such as the dispersibility of the silicon-based active material itself, which can maintain the connection between the active material even when the volume expands by using a rubber-based binder with high ductility, and the generation of gas from the slurry occurred.
[0009] In the end, a silicon-based negative electrode uses an aqueous binder. In order to solve the problems associated with using a silicon-based compound as a negative electrode active material, various methods are being discussed, such as a method for adjusting the driving potential, a method for additionally coating a thin film on the active material layer, a method for suppressing volume expansion itself, such as a method for adjusting the particle size of the silicon-based compound, or various methods for preventing the conductive path from being broken.
[0010] Nevertheless, the above-mentioned problems have not been solved. Given this situation, even when using a silicon-based anode to realize a high energy density, research is needed on a method for solving the problems of volume expansion and gas generation. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] Patent Publication No. 2009-080971 Summary of the Invention
Problems to be Solved by the Invention
[0012] It has been confirmed by research that in a silicon-based negative electrode, the silicon-based active material is hydrated by -OH groups on the surface, and gas is generated through electron transfer with carbon of the conductive material. Thus, it has been discovered that when using a specific combination of binders and performing surface treatment on the silicon-based negative electrode, the above problems can be solved.
[0013] Therefore, the present application relates to a negative electrode composition capable of solving the above problems, a negative electrode for a lithium secondary battery including the same, and a lithium secondary battery including the negative electrode.
Means for Solving the Problems
[0014] One embodiment of the present specification is a negative electrode composition including a silicon-based active material; a negative electrode conductive material; and a negative electrode binder, wherein the silicon-based active material includes one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), includes 70 parts by weight or more of the SiOx (x = 0) based on 100 parts by weight of the silicon-based active material, the silicon-based active material includes a carbon coating layer, the negative electrode binder includes a rubber-based binder; and an aqueous binder, and the content of the rubber-based binder is greater than the content of the aqueous binder.
[0015] In another embodiment, a negative electrode for a lithium secondary battery including a negative electrode current collector layer; and a negative electrode active material layer formed on one or both surfaces of the negative electrode current collector layer and including the negative electrode composition according to the present application is provided.
[0016] Finally, a lithium secondary battery including a positive electrode; the negative electrode for a lithium secondary battery according to the present application; a separator provided between the positive electrode and the negative electrode; and an electrolyte is provided.
Advantages of the Invention
[0017] It has been confirmed through research that in silicon-based negative electrodes, the silicon-based active material is hydrated by the -OH group on the surface, and gas is generated through electron transfer with the conductive carbon. Therefore, the negative electrode composition of the present invention includes a carbon coating layer on the surface of the silicon-based active material, which suppresses gas generation due to reaction with the -OH group, and has the characteristic of providing a negative electrode with improved performance due to excellent slurry stability.
[0018] Furthermore, in order to realize high energy density, the amount of conductive material is minimized, which leads to further insufficient conductive network between active materials during charging and discharging. To solve this problem, the negative electrode composition according to the present application contains a high content of rubber-based binder, which has excellent flexibility, compared to water-based binder, and can better maintain contact between silicon-based active materials. In addition, by minimizing the conductive material, the tortuosity of the voids in the negative electrode itself is improved, resulting in advantageous characteristics in terms of diffusion resistance.
[0019] That is, the negative electrode composition according to the present application is characterized in that the surface of the silicon-based active material is carbon-coated to enhance durability and to allow a large amount of rubber-based binder to be used. [Brief description of the drawings]
[0020] [Figure 1] FIG. 1 is a diagram showing a laminated structure of a negative electrode for a lithium secondary battery according to an embodiment of the present application. [Diagram 2] FIG. 1 is a diagram showing a stacked structure of a lithium secondary battery according to an embodiment of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] Before describing the present invention, some terms will first be defined. In this specification, when a part is said to "comprise" a certain component, this means that it may further include other components, rather than excluding other components, unless specifically stated to the contrary.
[0022] In this specification, "p to q" means a range of "not less than p and not more than q." In this specification, the "specific surface area" is measured by the BET method, specifically, calculated from the amount of nitrogen gas adsorption at liquid nitrogen temperature (77K) using a BELSORP-mini II manufactured by BEL Japan, Inc. That is, in this application, the BET specific surface area can mean the specific surface area measured by the above-mentioned measurement method.
[0023] In this specification, "Dn" means particle size distribution, and refers to the particle size at the n% point of the cumulative particle number distribution by particle size. That is, D50 is the particle size (median particle size) at the 50% point of the cumulative particle number distribution by particle size, D90 is the particle size at the 90% point of the cumulative particle number distribution by particle size, and D10 is the particle size at the 10% point of the cumulative particle number distribution by particle size. Meanwhile, the median particle size can be measured using a laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500), and the diffraction pattern difference due to the particle size when the particles pass through a laser beam is measured to calculate the particle size distribution.
[0024] In one embodiment of the present application, the grain size or particle size may refer to the average diameter or representative diameter of each grain constituting the metal powder.
[0025] In the present specification, when a polymer contains a certain monomer as a monomer unit, it means that the monomer is involved in a polymerization reaction and is contained as a repeating unit in the polymer. In the present specification, when a polymer contains a monomer, this is interpreted as the same as when a polymer contains a monomer as a monomer unit.
[0026] In this specification, unless otherwise specified as "homopolymer", the term "polymer" is understood to be used in a broad sense including copolymers. In this specification, the weight-average molecular weight (Mw) and the number-average molecular weight (Mn) are the polystyrene-equivalent molecular weights measured by gel permeation chromatography (GPC) using monodisperse polystyrene polymers (standard samples) of various degrees of polymerization commercially available for molecular weight measurement as standard substances. In this specification, unless otherwise specified, the molecular weight means the weight-average molecular weight.
[0027] Hereinafter, for those with ordinary knowledge in the technical field to which the present invention belongs to easily implement the present invention, a detailed description will be given with reference to the drawings. However, the present invention can be embodied in various different forms and is not limited to the following description.
[0028] One embodiment of this specification is a negative electrode composition containing a silicon-based active material; a negative electrode conductive material; and a negative electrode binder, wherein the silicon-based active material includes one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), based on 100 parts by weight of the silicon-based active material, SiOx (x = 0) is contained in an amount of 70 parts by weight or more, the silicon-based active material includes a carbon coating layer, the negative electrode binder includes a rubber-based binder; and an aqueous binder; and a negative electrode composition in which the content of the rubber-based binder is greater than the content of the aqueous binder is provided.
[0029] In one embodiment of this application, generally, a binder with excellent elongation characteristics is referred to as a rubber-based binder, the aqueous binder is well dispersed in an aqueous solvent such as water, the aqueous binder has hydrophilicity, and generally, it means a binder having the property of not being dissolved in an electrolyte or an electrolytic solution used in a secondary battery.
[0030] To achieve a high energy density, the amount of the conductive material is minimized, which results in a further shortage of the conductive network between the active materials during charge and discharge. To solve this problem, the negative electrode composition according to the present application contains a rubber-based binder with excellent flexibility in a larger amount relative to the aqueous binder, which can better maintain the contact between the silicon-based active materials. In addition, minimizing the conductive material improves the tortuosity of the voids in the negative electrode itself, making it have advantageous characteristics for diffusion resistance.
[0031] That is, in the case of the negative electrode composition according to the present application, the surface of the silicon-based active material is carbon-coated to enhance durability, and the content of the rubber-based binder can be applied in a larger amount.
[0032] In one embodiment of the present application, the silicon-based active material includes one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and provides a negative electrode composition containing 70 parts by weight or more of SiOx (x = 0) based on 100 parts by weight of the silicon-based active material.
[0033] In one embodiment of the present application, the silicon-based active material includes SiOx (x = 0), and provides a negative electrode composition containing 70 parts by weight or more of SiOx (x = 0) based on 100 parts by weight of the silicon-based active material.
[0034] In yet another embodiment, based on 100 parts by weight of the silicon-based active material, it may contain 70 parts by weight or more, preferably 80 parts by weight or more, more preferably 90 parts by weight or more of SiOx (x = 0), and may contain 100 parts by weight or less, preferably 99 parts by weight or less, more preferably 95 parts by weight or less.
[0035] The silicon-based active material according to the present application contains 70 parts by weight or more of the SiOx (x = 0) based on 100 parts by weight of the silicon-based active material, and has a characteristic that the theoretical capacity is higher than that of the silicon-based active material using the SiOx (0 < x < 2) series as the main substance. That is, when using the active material of the SiOx (0 < x < 2) series, no matter what treatment is performed on the active material itself, it is impossible to embody the same conditions as the charge and discharge capacity when having the silicon-based active material of the present invention.
[0036] In one embodiment of the present application, as the silicon-based active material, those containing particularly pure silicon (Si) particles can be used as the silicon-based active material. Using pure silicon (Si) particles as the silicon-based active material means, as described above, that when the silicon-based active material is based on 100 parts by weight in total, it can mean containing pure Si particles (SiOx (x = 0)) not combined with other particles or elements within the above range.
[0037] In one embodiment of the present application, the silicon-based active material may be composed of silicon-based particles having 100 parts by weight of SiOx (x = 0) based on 100 parts by weight of the silicon-based active material.
[0038] In one embodiment of the present application, the silicon-based active material may contain metal impurities. At this time, the impurities are metals that can generally be contained in the silicon-based active material. Specifically, it may contain 0.1 part by weight or less based on 100 parts by weight of the silicon-based active material.
[0039] In the case of the silicon-based active material, compared with the conventional graphite-based active material, the capacity is significantly higher, and the attempts to apply it are increasing. However, in the charge and discharge process, the silicon-based active material has a high volume expansion rate and is only used to the extent of being mixed with a small amount of the graphite-based active material.
[0040] Generally, silicon-based active materials are known to have a capacity 10 times higher than that of carbon-based active materials. Therefore, when silicon-based active materials are applied to a negative electrode, it is expected that an electrode having a high level of energy density even with a thin thickness can be realized.
[0041] Therefore, in the present invention, while only a silicon-based active material is used as the negative active material to improve capacity performance, the surface of the negative active material is coated with carbon and a specific binder is used in combination to solve problems such as the tortuosity of the electrode and the increase in diffusion resistance due to charge / discharge cycles.
[0042] In one embodiment of the present application, the silicon-based active material may include silicon-based particles having a particle size distribution of 0.01 μm or more and 30 μm or less.
[0043] The silicon-based active material containing silicon-based particles having a particle size distribution of 0.01 μm or more and 30 μm or less means that the silicon-based active material contains a large number of individual silicon-based particles having a particle size within the above range, and the number of silicon-based particles contained is not limited.
[0044] The particle size of the silicon-based particles may be expressed as a diameter when the particles are spherical, but when the particles are other than spherical, the particle size may be measured in comparison with the spherical particles, and the particle size of individual silicon-based particles may be measured by a method generally used in the art.
[0045] Meanwhile, the average particle size (D50) of the silicon-based active material of the present invention may be 5 μm to 10 μm, specifically 5.5 μm to 8 μm, and more specifically 6 μm to 7 μm. When the average particle size is within the above range, the specific surface area of the particles is within a proper range, and the viscosity of the negative electrode slurry is formed within a proper range. This allows smooth dispersion of the particles constituting the negative electrode slurry. In addition, when the size of the silicon-based active material is equal to or greater than the above lower limit range, the contact area between the silicon particles and the conductive material is excellent due to the complex of the conductive material and the binder in the negative electrode slurry, and the conductive network is more likely to be maintained, thereby increasing the capacity retention rate. Meanwhile, when the average particle size satisfies the above range, silicon particles that are too large are eliminated, and the surface of the negative electrode is formed smoothly, thereby preventing the non-uniformity of the current density during charging and discharging.
[0046] In one embodiment of the present application, the silicon-based active material generally has a characteristic BET specific surface area. The BET specific surface area of the silicon-based active material is preferably less than 0.01 m 2 / g~150.0m 2 / g, more preferably 0.1m 2 / g~100.0m 2 / g, particularly preferably 0.2m 2 / g~80.0m 2 / g, most preferably 0.2m 2 / g~18.0m 2 / g. The BET specific surface area is determined in accordance with DIN 66131 (with nitrogen).
[0047] In one embodiment of the present application, the silicon-based active material may be, for example, in crystalline or amorphous form, and is preferably not porous. The silicon particles are preferably spherical or shard-shaped particles. Alternatively, but less preferably, the silicon particles may also have a fibrous structure or be in the form of a film or coating that contains silicon.
[0048] In one embodiment of the present application, the carbon coating layer may be formed on the entire surface of the silicon-based active material.
[0049] In one embodiment of the present application, the carbon coating layer may be formed on a part of the silicon-based active material.
[0050] In one embodiment of the present application, the carbon coating layer may have a thickness of 0.1 μm or more and 10 μm or less.
[0051] In one embodiment of the present application, the silicon-based active material is 60 parts by weight or more based on 100 parts by weight of the negative electrode composition. In yet another embodiment, the silicon-based active material may be 60 parts by weight or more, preferably 65 parts by weight or more, more preferably 70 parts by weight or more, based on 100 parts by weight of the negative electrode composition, and may be 97 parts by weight or less, preferably 95 parts by weight or less, more preferably 90 parts by weight or less.
[0052] The negative electrode composition according to the present application has the characteristic that, when a silicon-based active material having a remarkably high capacity is used within the above range, the problem of increased resistance and the problem of reduced life can be solved by using a specific binder combination.
[0053] In one embodiment of the present application, the silicon-based active material may have a non-spherical morphology, and the sphericity is, for example, 0.9 or less, for example, 0.7 to 0.9, for example, 0.8 to 0.9, for example, 0.85 to 0.9.
[0054] In this application, the circularity is determined by the following formula 1, where A is the area and P is the perimeter. [Formula 1] 4πA / P 2
[0055] In the past, it was common to use only graphite-based compounds as negative electrode active materials, but recently, as the demand for high-capacity batteries has increased, attempts to mix and use silicon-based active materials to increase capacity have been increasing. However, in the case of silicon-based active materials, even if the properties of the silicon-based active material itself are adjusted as described above, the volume of the silicon-based active material rapidly expands during the charge / discharge process, which can cause some problems such as destruction of the conductive path formed in the negative electrode active material layer.
[0056] Therefore, in one embodiment of the present application, the negative electrode conductive material may include one or more selected from the group consisting of dot-like conductive materials, sheet-like conductive materials, and linear conductive materials.
[0057] In one embodiment of the present application, the dot-shaped conductive material may be used to improve the conductivity of the negative electrode, and refers to a conductive material in the form of a sphere or dots that has conductivity without inducing a chemical change. Specifically, the dot-shaped conductive material may be at least one selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide, and polyphenylene derivatives, and preferably includes carbon black in terms of realizing high conductivity and excellent dispersibility.
[0058] In one embodiment of the present application, the dot-shaped conductive material has a BET specific surface area of 40 m 2 / g or more 70m 2 / g or less, preferably 45m 2 / g or more 65m 2 / g or less, more preferably 50m 2 / g or more 60m 2 / g or less.
[0059] In one embodiment of the present application, the dot-like conductive material may have a functional group content (volatile matter) of 0.01% or more and 1% or less, preferably 0.01% or more and 0.3% or less, and more preferably 0.01% or more and 0.1% or less.
[0060] In particular, when the functional group content of the point-shaped conductive material satisfies the above range, when functional groups are present on the surface of the point-shaped conductive material and water is used as a solvent, the point-shaped conductive material can be smoothly dispersed in the solvent.
[0061] In one embodiment of the present application, the active material is characterized in that it contains, together with a silicon-based active material, a dot-shaped conductive material having a functional group content in the above-mentioned range, and the functional group content can be adjusted by the degree of heat treatment of the dot-shaped conductive material.
[0062] That is, in the production of point-shaped conductive materials, a high functional group content can mean that there is a lot of foreign matter, and a low functional group content can mean that more heat treatment processing has been performed.
[0063] In one embodiment of the present application, the particle diameter of the dotted conductive material may be 10 nm to 100 nm, preferably 20 nm to 90 nm, and more preferably 20 nm to 60 nm.
[0064] In one embodiment of the present application, the conductive material may include a sheet-shaped conductive material. The planar conductive material can improve conductivity by increasing surface contact between silicon particles in the negative electrode, and at the same time, can suppress the disconnection of the conductive path due to volume expansion, and can be expressed as a plate-shaped conductive material or a bulk-type conductive material.
[0065] In one embodiment of the present application, the sheet conductive material may include at least one selected from the group consisting of platelet graphite, graphene, graphene oxide, and graphite flakes, and may preferably be platelet graphite.
[0066] In one embodiment of the present application, the average particle size (D50) of the sheet conductive material may be 2 μm to 7 μm, specifically 3 μm to 6 μm, and more specifically 4 μm to 5 μm. If the range is satisfied, the particle size is sufficient to prevent excessive increase in viscosity of the negative electrode slurry, and dispersion is easy. Therefore, when dispersion is performed using the same equipment and time, the dispersion effect is excellent.
[0067] In one embodiment of the present application, there is provided a negative electrode composition in which the sheet conductive material has a D10 of 0.5 μm or more and 1.5 μm or less, a D50 of 2.5 μm or more and 3.5 μm or less, and a D90 of 7.0 μm or more and 15.0 μm or less.
[0068] In one embodiment of the present application, the sheet conductive material can be a high-specific surface area sheet conductive material having a high BET specific surface area; or a low-specific surface area sheet conductive material.
[0069] In one embodiment of the present application, the sheet conductive material may be a high-specific surface area sheet conductive material or a low-specific surface area sheet conductive material without any restrictions. However, since the sheet conductive material in the present application may be influenced to some extent by the electrode performance in terms of the effect of dispersion, it is particularly preferable to use a low-specific surface area sheet conductive material that does not cause dispersion problems.
[0070] In one embodiment of the present application, the sheet conductive material has a BET specific surface area of 5 m 2 / g or more.
[0071] In still another embodiment, the sheet conductive material has a BET specific surface area of 5 m 2 / g or more 500m 2 / g or less, preferably 5m 2 / g or more 300m 2 / g or less, more preferably 5m 2 / g or more 250m 2 / g or less.
[0072] In still another embodiment, the sheet conductive material is a high specific surface area sheet conductive material having a BET specific surface area of 50 m 2 / g or more 500m 2 / g or less, preferably 80m 2 / g or more 300m 2 / g or less, more preferably 100m 2 / g or more 300m 2 / g or less.
[0073] In still another embodiment, the sheet conductive material is a low specific surface area sheet conductive material having a BET specific surface area of 5 m 2 / g or more 40m 2 / g or less, preferably 5m 2 / g or more 30m 2 / g or less, more preferably 5m 2 / g or more 25m 2 / g or less.
[0074] Other conductive materials may include linear conductive materials such as carbon nanotubes. The carbon nanotubes may be bundled carbon nanotubes. The bundled carbon nanotubes may include a plurality of carbon nanotube units. Specifically, unless otherwise specified, the term "bundle type" refers to a secondary shape in which a plurality of carbon nanotube units are arranged or entangled with the longitudinal axis of the carbon nanotube units in substantially the same orientation, in the form of a bundle or rope. The carbon nanotube unit has a graphite sheet having a cylindrical shape with a nano-sized diameter and an sp2 bond structure. In this case, the graphite sheet may exhibit conductive or semiconductive properties depending on the angle and structure at which the graphite sheet is wound. The bundled carbon nanotubes may be uniformly dispersed during the manufacture of the negative electrode, and may smoothly form a conductive network in the negative electrode, thereby improving the conductivity of the negative electrode.
[0075] In one embodiment of the present application, the linear conductive material may include SWCNTs; or MWCNTs.
[0076] In one embodiment of the present application, there is provided a negative electrode composition, in which the negative electrode conductive material is 0.01 parts by weight or more and 40 parts by weight or less based on 100 parts by weight of the negative electrode composition.
[0077] In yet another embodiment, the negative electrode conductive material may comprise 0.01 parts by weight or more and 40 parts by weight or less, preferably 0.01 parts by weight or more and 30 parts by weight or less, and more preferably 0.05 parts by weight or more and 25 parts by weight or less, based on 100 parts by weight of the negative electrode composition.
[0078] In one embodiment of the present application, there is provided a negative electrode composition, wherein the negative electrode conductive material includes a planar conductive material and a linear conductive material.
[0079] In one embodiment of the present application, the negative electrode conductive material includes a sheet conductive material and a linear conductive material, and may include 0.01 parts by weight or more and 10 parts by weight or less of the linear conductive material and 90 parts by weight or more and 99.99 parts by weight or less of the sheet conductive material, based on 100 parts by weight of the negative electrode conductive material.
[0080] In yet another embodiment, the linear conductive material may be 0.01 parts by weight or more and 10 parts by weight or less, preferably 0.05 parts by weight or more and 5 parts by weight or less, and more preferably 0.1 parts by weight or more and 3 parts by weight or less, based on 100 parts by weight of the negative electrode conductive material.
[0081] In yet another embodiment, the sheet conductive material may be 90 parts by weight or more and 99.99 parts by weight or less, preferably 95 parts by weight or more and 99.95 parts by weight or less, and more preferably 97 parts by weight or more and 99.9 parts by weight or less, based on 100 parts by weight of the negative electrode conductive material.
[0082] In one embodiment of the present application, there is provided a negative electrode composition, in which the negative electrode conductive material includes a linear conductive material.
[0083] In particular, in order to realize high energy density, the amount of conductive material is minimized (only SWCNTs are used), which further reduces the conductive network between active materials during charging and discharging. To solve this problem, the negative electrode composition of the present application contains a higher content of rubber-based binder, which has excellent flexibility, compared to water-based binder, which can better maintain contact between silicon-based active materials. In addition, by minimizing the conductive material, the tortuosity of the voids in the negative electrode itself is improved, resulting in advantageous characteristics in terms of diffusion resistance.
[0084] The negative electrode conductive material according to the present application has a completely different structure from the positive electrode conductive material applied to the positive electrode. That is, the negative electrode conductive material according to the present application serves to provide a contact between silicon-based active materials, which have a very large volume expansion of the electrodes due to charging and discharging, and the positive electrode conductive material serves to provide some conductivity while acting as a buffer when rolled, and therefore has a completely different structure and role from the negative electrode conductive material of the present invention.
[0085] In addition, the negative electrode conductive material according to the present application is applied to a silicon-based active material, and has a completely different structure from a conductive material applied to a graphite-based active material. That is, a conductive material used in an electrode having a graphite-based active material has a property of improving output characteristics and imparting some conductivity because it simply has small particles compared to the active material, and has a completely different structure and role from a negative electrode conductive material applied together with a silicon-based active material as in the present invention.
[0086] In one embodiment of the present application, the planar conductive material used as the negative electrode conductive material generally has a structure and function different from that of a carbon-based active material used as a conventional negative electrode active material. Specifically, the carbon-based active material used as the negative electrode active material may be artificial graphite or natural graphite, and refers to a material that is processed into a spherical or dot-like shape to facilitate the storage and release of lithium ions.
[0087] On the other hand, the planar conductive material used as the negative electrode conductive material is a material having a planar or plate-like shape, and can be expressed as plate-like graphite. That is, it is a material contained in the negative electrode active material layer to maintain a conductive path, and does not play the role of storing and releasing lithium, but means a material to secure a conductive path in a planar state inside the negative electrode active material layer.
[0088] That is, in the present application, the use of plate-shaped graphite as a conductive material means that it is processed into a planar or plate-like shape and is used as a material that secures a conductive path, not to store or release lithium. In this case, the negative electrode active material contained therein has high capacity characteristics for storing and releasing lithium, and serves to store and release all lithium ions transferred from the positive electrode.
[0089] On the other hand, in the present application, the carbon-based active material is used as an active material, which means that the carbon-based active material is processed into a dot-like or spherical shape and is used as a material that serves to store or release lithium.
[0090] That is, in one embodiment of the present application, the carbon-based active material, artificial graphite or natural graphite, is in a dotted form and has a BET specific surface area of 0.1 m 2 / g or more 4.5m 2 / g or less. In addition, the plate-shaped graphite, which is a planar conductive material, may have a BET specific surface area of 5 m 2 / g or more.
[0091] In one embodiment of the present application, the negative electrode binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and substances in which hydrogen of these substances is substituted with Li, Na, Ca, or the like, or may include various copolymers thereof.
[0092] In one embodiment of the present application, there is provided a negative electrode composition, wherein the negative electrode binder includes a rubber-based binder and an aqueous binder, and the content of the rubber-based binder is greater than the content of the aqueous binder.
[0093] In one embodiment of the present application, the aqueous binder is one that can be dissolved in an aqueous solvent such as water, and includes at least one selected from the group consisting of polyvinyl alcohol (PVA), polyacrylic acid (PAA), polyethylene glycol (PEG), polyacrylonitrile (PAN) and polyacrylamide (PAM). In view of excellent resistance to volume expansion / contraction of the silicon-based active material, the aqueous binder may include at least one selected from the group consisting of polyvinyl alcohol and polyacrylic acid, more preferably polyvinyl alcohol and polyacrylic acid.
[0094] The aqueous binder may include a binder in which hydrogen in the aqueous binder is substituted with Li, Na, Ca, or the like in order to allow the aqueous binder to be better dispersed in an aqueous solvent such as water when preparing an aqueous slurry for forming an aqueous active material layer and to more smoothly coat the active material and improve binding strength.
[0095] The aqueous binder is hydrophilic and does not dissolve in electrolytes or electrolytic solutions generally used in secondary batteries. This characteristic can provide the aqueous binder with strong stress or tensile strength when applied to a negative electrode or lithium secondary battery, thereby effectively suppressing the problem of volume expansion / contraction of silicon-based active materials due to charging / discharging.
[0096] In one embodiment of the present application, there is provided a negative electrode composition, wherein the weight average molecular weight of the aqueous binder is 100,000 g / mol or more and 1,000,000 g / mol or less.
[0097] In one embodiment of the present application, the rubber-based binder is a substance different from the aqueous binder, and can be defined as a substance that is not well dissolved in an aqueous solvent such as water, but can be smoothly dispersed in an aqueous solvent. Specifically, the rubber-based binder may include at least one selected from the group consisting of styrene butadiene rubber (SBR), hydrogenated nitrile butadiene rubber (HNBR), acrylonitrile butadiene rubber, acrylic rubber, butyl rubber, and fluoro rubber, and may preferably include at least one selected from the group consisting of styrene butadiene rubber and hydrogenated nitrile butadiene rubber, more preferably styrene butadiene rubber, from the viewpoint of easy dispersion and excellent phase stability.
[0098] In one embodiment of the present application, the aqueous binder is a polymeric aqueous binder containing PAM, PAA, and PAN, and may be prepared by controlling the ratio of PAA and PAN to the PAM as a main component.
[0099] In the case of silicon-based active materials, the volume expansion is large and generally a rubber-based binder having excellent elongation properties should be used, but when this is used, there is a problem of gas generation from the slurry.
[0100] However, in the case of the negative electrode composition according to the present application, the problem of gas generation as described above is solved by carbon coating of the silicon-based active material, and thus the rubber-based binder is contained in a higher content than the water-based binder, and the problem of destruction of the conductive path due to the volume expansion of the silicon-based active material is solved.
[0101] In one embodiment of the present application, there is provided a negative electrode composition comprising, based on 100 parts by weight of the negative electrode binder, 55 parts by weight or more and 90 parts by weight or less of the rubber-based binder; and 10 parts by weight or more and 45 parts by weight or less of the water-based binder.
[0102] In still another embodiment, the negative electrode binder may contain 55 parts by weight or more and 90 parts by weight or less, preferably 55 parts by weight or more and 80 parts by weight or less, and more preferably 55 parts by weight or more and 70 parts by weight or less, based on 100 parts by weight of the negative electrode binder.
[0103] In still another embodiment, the negative electrode binder may contain 10 parts by weight or more and 45 parts by weight or less, preferably 20 parts by weight or more and 45 parts by weight or less, and more preferably 30 parts by weight or more and 45 parts by weight or less, based on 100 parts by weight of the negative electrode binder.
[0104] The negative electrode binder according to one embodiment of the present application plays a role in maintaining the active material and the conductive material to prevent distortion and deformation of the negative electrode structure due to volume expansion and relaxation of the silicon-based active material, and the above-mentioned problems can be solved by using the negative electrode binder having the above-mentioned composition and content.
[0105] In one embodiment of the present application, the negative electrode binder may be 30 parts by weight or less based on 100 parts by weight of the negative electrode composition.
[0106] In one embodiment of the present application, the amount of the negative electrode binder may be 30 parts by weight or less, preferably 25 parts by weight or less, and more preferably 20 parts by weight or less, based on 100 parts by weight of the negative electrode composition, and may be 5 parts by weight or more, or 10 parts by weight or more.
[0107] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, comprising: a negative electrode current collector layer; and a negative electrode active material layer formed on one or both sides of the negative electrode current collector layer, the negative electrode active material layer comprising the negative electrode composition according to the present application.
[0108] Fig. 1 is a diagram showing a laminated structure of a negative electrode for a lithium secondary battery according to one embodiment of the present application. Specifically, a negative electrode for a lithium secondary battery 100 including a negative electrode active material layer 20 on one surface of a negative electrode current collector layer 10 can be seen. Although Fig. 1 shows that the negative electrode active material layer is formed on one surface, it may be included on both surfaces of the negative electrode current collector layer.
[0109] In one embodiment of the present application, the negative electrode for a lithium secondary battery may be formed by applying a negative electrode slurry containing the negative electrode composition to one or both surfaces of a negative electrode current collector layer, and drying the applied slurry.
[0110] In this case, the negative electrode slurry may include the above-mentioned negative electrode composition and a slurry solvent.
[0111] In one embodiment of the present application, the solid content of the negative electrode slurry may be 5% or more and 40% or less.
[0112] In yet another embodiment, the solid content of the negative electrode slurry may satisfy the range of 5% to 40%, preferably 7% to 35%, and more preferably 10% to 30%.
[0113] The solid content of the negative electrode slurry may refer to the content of the negative electrode composition contained in the negative electrode slurry, and may refer to the content of the negative electrode composition based on 100 parts by weight of the negative electrode slurry.
[0114] When the solid content of the negative electrode slurry satisfies the above range, the viscosity during the formation of the negative electrode active material layer is appropriate, and the agglomeration of particles of the negative electrode composition is minimized, resulting in the efficient formation of the negative electrode active material layer.
[0115] In one embodiment of the present application, the slurry solvent may be used without limitation as long as it can dissolve the negative electrode composition. Specifically, water or NMP may be used.
[0116] In one embodiment of the present application, the negative electrode current collector layer generally has a thickness of 1 μm to 100 μm. Such a negative electrode current collector layer is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity, and for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. may be used. In addition, the binding force of the negative electrode active material can be strengthened by forming fine irregularities on the surface, and it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0117] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the negative electrode current collector layer has a thickness of 1 μm or more and 100 μm or less, and the negative electrode active material layer has a thickness of 20 μm or more and 500 μm or less.
[0118] However, the thickness is not limited thereto and may vary depending on the type and application of the negative electrode used.
[0119] In one embodiment of the present application, the porosity of the negative electrode active material layer may be in the range of 10% or more and 60% or less.
[0120] In still another embodiment, the porosity of the negative electrode active material layer may satisfy the range of 10% or more and 60% or less, preferably 20% or more and 50% or less, and more preferably 30% or more and 45% or less.
[0121] The porosity varies depending on the composition and content of the silicon-based active material, conductive material, and binder contained in the negative electrode active material layer. In particular, the silicon-based active material and conductive material according to the present application are contained in a specific composition and content, thereby satisfying the above range, and the electrode is characterized by having an appropriate range of electrical conductivity and resistance.
[0122] In one embodiment of the present application, there is provided a lithium secondary battery comprising: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator provided between the positive electrode and the negative electrode; and an electrolyte.
[0123] 2 is a diagram showing a laminated structure of a lithium secondary battery according to an embodiment of the present application. Specifically, a lithium secondary battery anode 100 including an anode active material layer 20 on one side of an anode current collector layer 10 can be seen, and a lithium secondary battery cathode 200 including a cathode active material layer 40 on one side of a cathode current collector layer 50 can be seen, and the lithium secondary battery anode 100 and the lithium secondary battery cathode 200 are laminated with a separator 30 interposed therebetween.
[0124] A secondary battery according to an embodiment of the present specification may include the negative electrode for a lithium secondary battery described above. Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator and an electrolyte interposed between the positive electrode and the negative electrode, and the negative electrode is the same as the negative electrode described above. The negative electrode has been described above, so a detailed description thereof will be omitted.
[0125] The positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector and including the positive electrode active material.
[0126] In the positive electrode, the positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, etc. may be used. In addition, the positive electrode current collector may usually have a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the collector surface to increase the adhesive force of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0127] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; a lithium iron oxide such as LiFe3O4; 1+c1 Mn 2-c1 O4 (0≦c1≦0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5, Cu2V2O7; chemical formula LiNi 1-c2 M c2 Ni-site type lithium nickel oxide represented by the chemical formula LiMnO2 (wherein M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B and Ga, and satisfies 0.01≦c2≦0.3);2-c3 M c3 Examples of the lithium manganese composite oxide include, but are not limited to, lithium manganese composite oxide represented by Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn, and Ta, and satisfies 0.01≦c3≦0.1) or Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu, and Zn); LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion. The positive electrode may be metallic lithium (Li-metal).
[0128] The positive electrode active material layer may contain a positive electrode conductive material and a positive electrode binder in addition to the positive electrode active material described above.
[0129] In this case, the positive electrode conductive material is used to give conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery that is constructed.Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in mixture.
[0130] The positive electrode binder plays a role of improving the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the positive electrode current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one or more of these may be used alone or in combination.
[0131] The separator is a separator that separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is generally used as a separator in a secondary battery may be used without any particular limitation. In particular, a separator that has low resistance to ion movement of the electrolyte and excellent electrolyte moisture absorption ability is preferable. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting point glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, a coated separator containing a ceramic component or a polymeric substance may be used to ensure heat resistance or mechanical strength, and may be selectively used in a single layer or multilayer structure.
[0132] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the manufacture of lithium secondary batteries, but are not limited to these. Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.
[0133] Examples of the non-aqueous organic solvent include N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, gamma-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and non-quantum organic solvents such as ethyl propionate.
[0134] In particular, ethylene carbonate and propylene carbonate, which are cyclic carbonates among the carbonate-based organic solvents, are preferably used because they are high-viscosity organic solvents with high dielectric constants and good dissociation of lithium salts. When such cyclic carbonates are mixed in an appropriate ratio with chain carbonates having low viscosity and low dielectric constants such as dimethyl carbonate and diethyl carbonate, an electrolyte having high electrical conductivity can be produced, and these are further preferably used.
[0135] The metal salt may be a lithium salt. The lithium salt is a substance that is easily dissolved in the non-aqueous electrolyte. For example, the anion of the lithium salt is F - , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF- , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - One or more selected from the group consisting of may be used.
[0136] In addition to the constituents of the electrolyte, the electrolyte may further include one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, and aluminum trichloride for the purpose of improving the life characteristics of the battery, suppressing a decrease in battery capacity, and improving the discharge capacity of the battery.
[0137] According to an embodiment of the present invention, there is provided a battery module including the secondary battery as a unit cell, and a battery pack including the battery module. The battery module and the battery pack include the secondary battery having high capacity, high rate-limiting characteristics and high cycle characteristics, and can be used as a power source for medium- to large-sized devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.
[0138] Below, preferred embodiments are presented to aid in understanding the present invention. However, these embodiments are merely illustrative of the present description, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical ideas of the present description. Naturally, such changes and modifications fall within the scope of the appended claims. EXAMPLES
[0139] <Production Example> <Production of negative electrode composition> Negative electrode compositions satisfying the compositions and contents in Table 1 below were prepared.
[0140] [Table 1]
[0141] In Table 1, the silicon-based active materials are Si (average particle size (D50): 3.5 μm), SiO (average particle size (D50): 6.0 μm), and SiC (average particle size (D50): 8.5 μm), and the plate-shaped conductive material A is a silicon-based active material having a BET specific surface area of 17 m 2 / g, D10: 1.7 μm, D50: 3.5 μm, D90: 6.8 μm, and the BET specific surface area of SWCNT is 1000 m 2 / g~1500m 2 / g and an aspect ratio of 10,000 or more were used.
[0142] The PAM (Polyacrylamide) binder has a weight average molecular weight (Mw) of 500,000 g / mol to 800,000 g / mol, a number average molecular weight (Mn) of the order of 100,000 to 400,000, and a PDI value of 20 to 50.
[0143] The binder was in an aqueous form, and the weight average molecular weight and number average molecular weight were measured using aqueous GPC (gel permeation chromatography).
[0144] Anode manufacturing The negative electrode composition having the composition shown in Table 1 was added to distilled water as a solvent for forming a negative electrode slurry to prepare a negative electrode slurry (solid concentration: 25 wt %).
[0145] After this, the negative electrode loading amount was 76.34 mg / 25 cm with a thickness of 38 μm on a copper foil (Cu foil) with a thickness of 8 μm. 2 After coating the negative electrode active material layer, the negative electrode was dried at 130° C. for 12 hours and rolled to a negative electrode porosity of 40% to prepare a negative electrode.
[0146] For reference, in Comparative Examples 6 to 8 in which the type of active material was different, the negative electrode and secondary battery were not manufactured as described below, and the amount of generated slurry gas and the capacity of the active material through CHC manufacturing were compared and shown in Table 2.
[0147] <Secondary battery manufacturing> LiNi as the positive electrode active material 0.6 Co 0.2 Mn 0.2 O2 (average particle size (D50): 15 μm), carbon black (product name: Super C65, manufacturer: Timcal) as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were added in a weight ratio of 97:1.5:1.5 to N-methyl-2-pyrrolidone (NMP) as a solvent for forming a positive electrode slurry to prepare a positive electrode slurry (solid concentration 78 wt%).
[0148] The positive electrode slurry was applied to both sides of an aluminum current collector (thickness: 12 μm) at a rate of 537 mg / 25 cm. 2 The coated layer was rolled and dried in a vacuum oven at 130° C. for 10 hours to form a positive electrode active material layer (thickness: 65 μm) to prepare a positive electrode (thickness of positive electrode: 77 μm, porosity: 26%).
[0149] A polyethylene separator was interposed between the positive electrode and the negative electrode of each of the examples and comparative examples, and an electrolyte was injected between the positive electrode and the negative electrode to prepare a lithium secondary battery.
[0150] The electrolyte was prepared by adding 3% by weight of vinylene carbonate based on the total weight of the electrolyte to an organic solvent in which fluoroethylene carbonate (FEC) and diethyl carbonate (DEC) were mixed in a volume ratio of 10:90, and LiPF6 was added as a lithium salt at a concentration of 1M.
[0151] Experimental Example 1: Measurement of negative electrode slurry gas generation rate 5 g of the prepared negative electrode slurry was put into a 5 cm x 5 cm aluminum pouch, sealed, and then stored in an oven at 60°C for 24 hours. The pouch was then placed in a graduated cylinder to measure the volume change and the amount of gas generated. The results are shown in Table 2 below.
[0152] Experimental example 2: Evaluation of mono cell room temperature life characteristics (4.2-3.0V) The secondary batteries including the negative electrodes prepared in the Examples and Comparative Examples were subjected to a life evaluation using an electrochemical charger / discharger, and the capacity retention rate was evaluated. The secondary batteries were subjected to a cycle test at 4.2-3.0V 1C / 0.5C, and the number of cycles at which the capacity retention rate reached 80% was measured.
[0153] Capacity retention rate (%) = {(discharge capacity at Nth cycle) / (discharge capacity at 1st cycle)} x 100 The results are shown in Table 2 below.
[0154] Experimental Example 3: Evaluation of mono-cell resistance increase rate measurement (250 cycles, @SOC50%, discharge) In the test of Experimental Example 2, the capacity retention rate was measured by charging / discharging at 0.33C / 0.33C (4.2-3.0V) every 50 cycles, and then the resistance was measured by discharging at 2.5C pulse at SOC50, and the resistance increase rate was compared and analyzed.
[0155] Furthermore, data at 250 cycles was calculated for each of the life characteristic evaluation and the resistance increase rate measurement evaluation, and the results are shown in Table 2 below.
[0156] [Table 2]
[0157] From the results in Table 2, it can be seen that the negative electrode composition of the present invention includes a carbon coating layer on the surface of the silicon-based active material, which suppresses gas generation due to reaction with -OH groups, and thus not only has excellent slurry stability but also improved performance.
[0158] Furthermore, in order to realize high energy density, the amount of conductive material is minimized, which leads to further insufficient conductive network between active materials during charging and discharging. To solve this problem, the negative electrode composition according to the present application contains a high content of rubber-based binder, which has excellent flexibility, compared to water-based binder, and can better maintain contact between silicon-based active materials. In addition, by minimizing the conductive material, it has been confirmed that the tortuosity of the voids in the negative electrode itself is improved, and the composition has advantageous characteristics in terms of diffusion resistance.
[0159] Specifically, by checking the gas generation amount in Table 2, it was confirmed that the surface of the silicon-based active material is protected by carbon coating, so the gas generation amount is reduced, and the amount of gas generation increases as the amount of conductive material increases. That is, when comparing Example 2 with Example 1 and Comparative Example 5, it was confirmed that the gas generation amount is greater than that of Example 1, and that the gas generation amount is suppressed in Example 2 compared to Comparative Example 5 because the surface is coated with carbon.
[0160] In addition, Comparative Examples 6 to 9 are cases where an active material of SiO or SiC is used instead of pure silicon (Pure Si) as in the present invention, and in these cases, Si exists in nano-size, and the amount of gas generated is greater than in the Examples, and even if a carbon coating treatment is performed as in Comparative Examples 8 and 9, the amount of gas generated is greater than in the Examples, and problems occur. In addition, Comparative Examples 6 to 9 are cases where a different active material is used, and in these cases, the capacity is very small compared to the Examples, and to realize the same energy density, the loading becomes very high, and problems may occur in fast charging, etc.
[0161] Furthermore, it was confirmed that in the case of the carbon-coated silicon-based active material, the electrical conductivity also increased and the rate of increase in resistance decreased compared to the case without the carbon coating. [Explanation of symbols]
[0162] 10 Negative electrode current collector layer 20...Negative electrode active material layer 30 Separator 40...Cathode active material layer 50 Positive electrode current collector layer 100 ···Negative electrode for lithium secondary battery 200 ···Positive electrode for lithium secondary batteries
Claims
1. A negative electrode composition comprising a silicon-based active material, a negative electrode conductive material, and a negative electrode binder, The silicon-based active material includes one or more selected from the group consisting of SiOx (x=0) and SiOx (0<x<2), and includes 70 parts by weight or more of the SiOx (x=0) based on 100 parts by weight of the silicon-based active material; The silicon-based active material includes a carbon coating layer, the negative electrode binder includes a rubber-based binder and a water-based binder, The negative electrode composition, wherein the content of the rubber-based binder is greater than the content of the water-based binder.
2. The negative electrode composition according to claim 1 , wherein the carbon coating layer is formed on the entire surface of the silicon-based active material.
3. The negative electrode composition according to claim 1 , wherein the silicon-based active material is present in an amount of 60 parts by weight or more based on 100 parts by weight of the negative electrode composition.
4. The negative electrode composition according to claim 1 , wherein the negative electrode conductive material comprises at least one selected from the group consisting of a dot-like conductive material, a sheet-like conductive material, and a linear conductive material.
5. The negative electrode composition of claim 1 , wherein the negative electrode binder is present in an amount of 30 parts by weight or less based on 100 parts by weight of the negative electrode composition.
6. The negative electrode composition according to claim 1 , comprising, based on 100 parts by weight of the negative electrode binder, 55 parts by weight or more and 90 parts by weight or less of the rubber-based binder and 10 parts by weight or more and 45 parts by weight or less of the water-based binder.
7. The negative electrode composition according to claim 1 , wherein the carbon coating layer has a thickness of 0.1 μm to 10 μm.
8. A negative electrode current collector layer, and A negative electrode active material layer comprising the negative electrode composition according to any one of claims 1 to 7, which is formed on one or both sides of the negative electrode current collector layer. A negative electrode for a lithium secondary battery comprising:
9. The negative electrode current collector layer has a thickness of 1 μm or more and 100 μm or less, 9. The negative electrode for a lithium secondary battery according to claim 8, wherein the negative electrode active material layer has a thickness of 20 μm or more and 500 μm or less.
10. positive electrode, The negative electrode for a lithium secondary battery according to claim 8 . A separator provided between the positive electrode and the negative electrode; and electrolyte, A lithium secondary battery comprising:
Citation Information
Patent Citations
Negative electrode material, negative plate and preparation method of negative plate, lithium-ion battery and preparation method of lithium-ion battery
CN108306006A
Silicon-containing negative pole piece and lithium ion battery containing same
CN114613942A
Anode for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery
JP2007165078A
Negative electrode for nonaqueous electrolyte secondary battery, method for manufacturing the same, and nonaqueous electrolyte secondary battery
JP2015069712A
Negative electrode and power storage device
JP2015179592A
Cited By
Method of detecting a concealed pattern
US12380306B2